Comparison of balance strategies in mountain climbers during real altitude exposure between 1.500 m and 3.200 m: Effects of age and expertise. (14th September 2017) - Bruyneel, Anne-Violette; Humbert, Arnaud; Bertrand, Marc
Highlights: Eighty-nine volunteer mountaineers were tested at 1500 m and 3200 m. At 1500 m there were no effects of age and expertise. At 3200 m, postural control was disturbed. At 3200 m, higher age and lower expertise decreased stability Abstract: Purpose: The aim of this study was to estimate the effect of altitude (1500 m vs. 3200 m) on balance strategies, and to determine the influence of age (> or <40 years) and expertise (> or <20 days of mountain climbing/year) on postural stability at altitude. Method: Eighty-nine volunteer mountaineers were tested at 1500 m, 3200 m immediately after exiting the cable car and at 3200 m following the climb and return. Double-leg stance with eyes closed and single-leg stance with eyes open were tested. The center of pressure (CoP) was recorded for 12.8 s using a stabilometric force platform. Length, surface, ratio (length/surface), and average speed of the CoP, as well as lower limb loading were calculated. Groups and altitudes were compared using ANOVA. Significance was set to p < 0.05. Results: CoP ratio was significantly higher during both balance conditions at 3200 m compared to 1500 m (p < 0.05). Lower limb loading was symmetrical at 1500 m but not at 3200 m (p < 0.05). There was no influence of age or expertise at 1500 m (p = NS), however at 3200 m, older subjects and subjects with less expertise had greater length and surface of the CoP, showing more instability (p < 0.05). Conclusion: Postural stability was immediately reduced on arrival at 3200 m, particularly in subjects above the age of 40 years with less expertise.